Redescriptions of two poorly known deep-sea shrimps (Crustacea: Decapoda: Caridea: Pasiphaeidae and Glyphocrangonidae) from the Andaman Sea, eastern Indian Ocean - Komai, Tomoyuki; Chan, Tin-Yam (Zootaxa, 2017)
Two deep-sea caridean shrimps are reported on the basis of topotypic materials recently collected from the Andaman Sea off Myanmar, eastern Indian Ocean: Pasiphaea unispinosa Wood-Mason, 1892 (Pasiphaeidae) and Glyphocrangon smithii Wood-Mason & Alcock, 1891b (Glyphocrangonidae). These two taxa are poorly known in literature, and thus their diagnostic features remain to be reassessed. The present material enabled us to describe morphological characters of the two species in detail, even though only a single specimen is available for each species. Pasiphaea unispinosa closely resembles P. merriami Schmitt, 1931 from the western Atlantic, but the distinctly carinate middorsal carapace, the deep branchiostegal sinus and the different structure of the pleonal tergites distinguish P. unispinosa from P. merriami. Glyphocrangon smithii is most similar to G. amblytes Komai, 2004 from the western Indian Ocean and G. wagini from Sala y Gomez Ridge in the eastern Pacific, but it is distinctive in having an unusually deep longitudinal groove on the extensor surface of each pereopod 4 and 5 dactylus.